Aplikasi Rsm Untuk Optimasi Suhu Dan Waktu Pada Proses Pelarutan Silika Dari Pomfa Dengan Reaktor Hidrotermal - Eri Kaiyul; Edy Saputra; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Response Surface Methodology (RSM) is a set of mathematical and statistical techniques that are useful for analyzing problems where several independent variables influence response. The ultimate goal of RSM is for optimizing response. The aim of this study to determine the optimal process conditions in the silica extraction process from POMFA by using Response Surface Methodology (RSM). Silica was extracted by reacting fly ash with NaOH and aquadest. The optimized variables were temperature of 120°C (low) and 150°C (high) and time of 4 hour (low) and 6 hour (high). The silica extract was precipitated using HCl 10% at temperature of 30°C; stirring speed of 500 rpm and pH 9. The silica gel was analyzed using XRF to determine chemical composition. The silica yield were calculated from the chemical composition obtained. RSM-CCD was applied to optimize the extraction process using software Minitab 16.1.1.Keywords: extraction, optimum, POMFA, RSM, silica